Implementasi Instrumen Asesmen Keterampilan Menulis Cerpen dengan Media Lagu Inspiratif untuk Siswa Kelas XI SMA di Era Merdeka Belajar - Santoso, Redin Surya Bagas; Suyono, Suyono; Harsiati, Titik; Sari, Nia Puspita (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The formulation of educational programs has a progressive impact on the learning climate, regardless of the rules that are coherent-implementative in the current teaching and learning process. Permendikbudristek Regulation No. 56 of 2022 concerning the restoration of the independent learning curriculum policy is systematically integrated in learning assessment and teacher workload capacity, the independent curriculum basically functions as the freedom of students to choose the learning curriculum in accordance with the learning assessment. Therefore, teacher creativity is needed to determine the needs of students and learning outcomes. The method used in this research uses qualitative methods with a case study approach. The purpose of this study describes (1) the form and construction of short story writing skills assessment instruments with the use of inspirational song media for grade XI students, (2) the implementation of writing assessments using inspirational song media, and media based on life values and as a creative-inspiring means for students in writing activitie and (3) obstacles faced by students and teachers in learning to write short stories. The use of short story writing assessment using song media is realized as a complementary means for teachers to determine the power of student writing competence. Writing assessment and short story writing assessment rubrics are designed, to assist in measuring student learning outcomes through learning activities using song media based on life values and as a creative-inspiring means for students in writing activities.